A Study on Consumers’ Preferences for the Palace Museum’s Cultural and Creative Products from the Perspective of Cultural Sustainability - Tu, Jui-Che; Liu, Li-Xia; Cui, Yang (Sustainability, 2019)
In recent years, the development and design of the cultural and creative products of the Palace Museum in Beijing have become a hot topic in the product design field. Many critics have pointed out that cultural and creative products have failed to faithfully convey the implied meanings of the cultural stories of the Palace Museum. To effectively narrow the cognitive gap between designers and consumers, designers must urgently clarify the relationship between different design attributes and consumer preferences. The questionnaires were used to obtain data from 297 subjects. Through SPSS statistical software, the results were analyzed by descriptive statistics, explore factor analysis (EFA), independent sample t-test, and ANOVA to explore consumers’ attitudes and preferences on the Palace Museum’s cultural and creative products. The results showed that consumers attach great importance to factors such as “cultural connotation” and “unique creativity” when choosing the Palace Museum’s cultural and creative products. The consumer in different genders had significant differences in the design factors of the Palace Museum’s cultural and creative products. There were significant differences in the factors of “Forbidden City culture”, “cultural sustainability” and “traditional culture” to different educational backgrounds. There were significant differences in the factor of “Forbidden City culture” to different ages. There were significant differences in the factors of “cultural traits” and “cultural identity” between the with and without a design background groups. The results of this study will identify the key factors for the design of the Palace’s Museum cultural and creative products and provide references for designers.